2015
DOI: 10.1371/journal.pone.0118163
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Significance of Cerebral Microbleeds Locations in CADASIL with R544C NOTCH3 Mutation

Abstract: Background and PurposeAlthough cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common single-gene disorder of cerebral small blood vessels caused by NOTCH3 mutations, little has been described about the variation in the clinical findings between its underlying types of mutations. In particular, the presence of cerebral microbleeds (CMBs) has been an increasingly recognized magnetic resonance imaging finding in CADASIL, but their clinical signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
1
27
0
3
Order By: Relevance
“…Not only VSMC but also pericytes may be affected in CADASIL, as recent data show that pericytes accumulate GOM in CADASIL patients (229), and in keeping with a perturbed pericyte function, small hemorrhages are observed in CADASIL patients (399). Furthermore, some of the effects observed in the Notch3 Ϫ/Ϫ ; Notch1 ϩ/Ϫ mice may be linked to dysregulated pericytes (355).…”
Section: A Monogenic Diseases Caused By Mutations In the Notch Pathwaymentioning
confidence: 99%
“…Not only VSMC but also pericytes may be affected in CADASIL, as recent data show that pericytes accumulate GOM in CADASIL patients (229), and in keeping with a perturbed pericyte function, small hemorrhages are observed in CADASIL patients (399). Furthermore, some of the effects observed in the Notch3 Ϫ/Ϫ ; Notch1 ϩ/Ϫ mice may be linked to dysregulated pericytes (355).…”
Section: A Monogenic Diseases Caused By Mutations In the Notch Pathwaymentioning
confidence: 99%
“…Unlike in an earlier study 4 in which we found a significant difference in the number of lobar CMB between patients aged ≥60 years and those aged <60 years but not in the number of deep or infra-tentorial CMB, our more recent results demonstrated no association between age and presence of lobar CMB. 3 This discrepancy may in part reflect the different assessment methods used in the two mentioned studies. First, we have now used more sensitive MRI techniques to detect CMBs than those used previously: the effects of MRI sequences (traditional T2*-weighted gradient echo vs. SWI); section thickness (5 mm vs. 2 mm); and field strength (1.5 tesla vs. 3 tesla).…”
Section: Discussionmentioning
confidence: 98%
“…Second, in the present study, we used the MARS 10 system to calculate CMB. However, in our previous study, 3 we divided CMBs into five groups according to brain location (cortical-subcortical, basal ganglia, thalamus, brain stem, and cer-ebellum) and then calculated the number of CMBs. In addition, SWI, smaller section thickness, and a higher magnetic field are known to increase the number of CMBs detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinically relevant data can also be extrapolated from other more 'pure' clinical cohorts. For example, in CADASIL, a 'pure' form of small vessel disease and vascular dementia (with affected individuals progressing to dementia at 40-60 years of age), the presence of coexistent Alzheimer's disease pathology and CAA in unlikely: microbleeds frequently occur in the cerebellum and are associated with symptomatic stroke presentation [10,11] .…”
mentioning
confidence: 99%